2018
DOI: 10.4236/ce.2018.915188
|View full text |Cite
|
Sign up to set email alerts
|

Pen Pals Are Now in Your Finger Tips— A Global Collaboration Online Project to Develop Writing Skills

Abstract: Many Malaysian students have an aversion towards writing. This study explores the potential of using an online material entitled, PenPal Schools, in the English as Second Language (ESL) classroom to develop writing skill with peers around the world via an online collaborative project. A research was carried out to provide insights into the aspects of PenPal Schools that are useful in developing writing skills and to find out the potential of this material as a teaching and learning tool in writing lessons. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In addition, this innovation gives teachers more contact hours with the students in Telegram in a very feasible, interactive, interesting and less-stressed medium. Lie and Yunus (2018) support the idea of all educators should clinch to authentic materials to help our students to enhance their English language skills outside of the classroom.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, this innovation gives teachers more contact hours with the students in Telegram in a very feasible, interactive, interesting and less-stressed medium. Lie and Yunus (2018) support the idea of all educators should clinch to authentic materials to help our students to enhance their English language skills outside of the classroom.…”
Section: Discussionmentioning
confidence: 86%
“…Hence, it is crucial for teachers to put high priority on learners' interests and learning preferences in selecting the best educational tools in teaching and learning. If applications like Telegram and Quizlet are utilized its use to the maximum, teaching and learning will be more engaging, interactive, feasible, and inspiring as according to Lie and Yunus (2018), learning starts with engagement. In addition, Qgram innovation indirectly lessens teachers' workload as Quizlet automatically generates the result for students to review with the teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online learning has long become an alternative mode of instruction, providing another option of learning for individuals who cannot attend a regular classroom for specific reasons (Gemin & Pape, 2017). Some studies had also reported that this learning instruction model provides learners with some advantages including the exercise of autonomy (Ardi, 2017), learner-centered, and global connection by having collaboration with other language learners or native speakers (Lee & Kim, 2018;Lie & Yunus, 2018).…”
Section: Students' Perception Of Online Learningmentioning
confidence: 99%
“…However, English is the second language in Malaysia. Lie and Yunus (2018) also mentioned that English is the global language of interaction. It is crucial for a person's competencies development.…”
Section: Introductionmentioning
confidence: 99%